Dietary choices are influenced by genotype, mating status, and sex in Drosophila melanogaster. Issue 11 (2nd May 2018) - Camus, M. Florencia; Huang, Chun‐Cheng; Reuter, Max; Fowler, Kevin
Abstract: Mating causes many changes in physiology, behavior, and gene expression in a wide range of organisms. These changes are predicted to be sex specific, influenced by the divergent reproductive roles of the sexes. In female insects, mating is associated with an increase in egg production which requires high levels of nutritional input with direct consequences for the physiological needs of individual females. Consequently, females alter their nutritional acquisition in line with the physiological demands imposed by mating. Although much is known about the female mating‐induced nutritional response, far less is known about changes in males. In addition, it is unknown whether variation between genotypes translates into variation in dietary behavioral responses. Here we examine mating‐induced shifts in male and female dietary preferences across genotypes of Drosophila melanogaster . We find sex‐ and genotype‐specific effects on both the quantity and quality of the chosen diet. These results contribute to our understanding of sex‐specific metabolism and reveal genotypic variation that influences responses to physiological demands. Abstract : Here we examine mating‐induced shifts in male and female dietary preferences across genotypes of Drosophila melanogaster . This was done by giving flies of each sex/genotype a choice in protein and carbohydrate consumption. We find sex‐ and genotype‐specific effects on both the quantity and quality of the chosen diet. These results contribute to our understanding of sex‐specific metabolism and reveal genotypic variation that influences responses to physiological demands.